Survivors of the Shoah: Interviewee: Emery Robert Part I (Survivors of the Shoah Visual History Foundation, 1998)
Shoah Foundation interview code: 42664 Duration: 01:54:00 Interview with Holocaust survivor Emery Robert. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Sandy Rebitzer.